The European Union’s Trade Strategy and Its Reflections on Turkey: an Evaluation from the Perspective of Free Trade Agreements - Sait AKMAN (Dokuz Eylül Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2010)
This study attempts to assess implications, of European Union’s (EU) new trade strategy and its Free Trade Agreements (FTAs) with third countries, on Turkey-EU relations. It analyses critics raised in the context of FTAs and puts forward that the sustainability of the relations is contingent to the satisfaction of a set of criteria.The EU shifted its trade policy from sole reliance on multilateral trade negotiations towards initiatives for bilateral and preferential agreements (PTAs) under its ‘Global Europe’ strategy which was adopted in 2006, to propose its trade policy agenda and priorities in accordance with its Lisbon Strategy. WTO Doha Round is currently in deadlock and it is improbable that it will be concluded in the near future. Partly for this reason, the EU tends to implement its policy objectives constantly through a set of FTAs. Turkey has to align its trade policy to the EU’s preferential regimes, pursuant to its obligations arising from the Customs Union (CU). Hence, it has concluded so far sixteen FTAs with relevant countries. On the other hand, the intensification of critics about the FTAs process and the CU brings impediments for Turkey to commit itself to its CU obligations in the next period. Two main motives can be cited as a reason: First, the EU trade strategy obviously considers the global context within which the EU rests; and the Member States’ interests, which are subsequently reflected into its FTAs. Nevertheless, a harmonious action by Turkey becomes onerous as long as EU trade priorities diverge from Turkey’s long term trade strategy. Second reason, aside from technical aspects of the CU, can be attributed to the ‘political uncertainty’ converged around the ‘open-endedness’ of the membership process, which in turn affects the CU, Turkey’s most vital linkage to the EU, and the commitments there from.